Comparative phylogeography of five widespread tree species: Insights into the history of western Amazonia. Issue 12 (11th June 2019) - Honorio Coronado, Eurídice N.; Dexter, Kyle G.; Hart, Michelle L.; Phillips, Oliver L.; Pennington, R. Toby
Abstract: Various historical processes have been put forth as drivers of patterns in the spatial distribution of Amazonian trees and their population genetic variation. We tested whether five widespread tree species show congruent phylogeographic breaks and similar patterns of demographic expansion, which could be related to proposed Pleistocene refugia or the presence of geological arches in western Amazonia. We sampled Otoba parvifolia/glycycarpa (Myristicaceae), Clarisia biflora, Poulsenia armata, Ficus insipida (all Moraceae), and Jacaratia digitata (Caricaceae) across the western Amazon Basin. Plastid DNA ( trn H– psb A; 674 individuals from 34 populations) and nuclear ribosomal internal transcribed spacers (ITS; 214 individuals from 30 populations) were sequenced to assess genetic diversity, genetic differentiation, population genetic structure, and demographic patterns. Overall genetic diversity for both markers varied among species, with higher values in populations of shade‐tolerant species than in pioneer species. Spatial analysis of molecular variance (SAMOVA) identified three genetically differentiated groups for the plastid marker for each species, but the areas of genetic differentiation were not concordant among species. Fewer SAMOVA groups were found for ITS, with no detectable genetic differentiation among populations in pioneers. The lack of spatially congruent phylogeographic breaks across species suggests no common biogeographic history of these Amazonian tree species. The idiosyncratic phylogeographic patterns of species could be due instead to species‐specific responses to geological and climatic changes. Population genetic patterns were similar among species with similar biological features, indicating that the ecological characteristics of species impact large‐scale phylogeography. Abstract : Our study includes thorough and relatively uniform sampling of populations of five widespread western Amazonian tree species across a wide geographic area covering most of western Amazonia. As such, it is the first comparative phylogeographic study of the trees of western Amazonia, which houses the world's most species‐rich forests. By using plastid and nuclear markers sampled in 34 locations across Ecuador, Peru, and Bolivia, we studied the geographic patterns of genetic differentiation to test for shared impact of past climatic and geological events. We did not find spatially congruent phylogeographic breaks across species suggesting no common biogeographic history of these Amazonian tree species. The idiosyncratic phylogeographic patterns of species could be due instead to species‐specific responses to geological and climatic changes. Population genetic patterns were similar among species with similar biological features, indicating that the ecological characteristics of species impact large‐scale phylogeography.